Clozapine and tuberculosis treatment: a case report and literature review - Swamy, Neel; Jepsen, Jennifer; Werth, Brian J.; Sunshine, Anna; English, Clayton (Frontiers in Psychiatry, 2025)
IntroductionTo date, clozapine is the only antipsychotic approved by the United States Food and Drug Administration (FDA) for the management of treatment-resistant schizophrenia. People with serious mental illness are at higher risk of developing tuberculosis and have worse tuberculosis recovery outcomes compared to the general population. First-line regimens for acute tuberculosis often include rifamycins and isoniazid, both of which impact clozapine metabolism and levels through induction or inhibition of the hepatic cytochrome P450 (CYP450) enzyme system. There is limited evidence, mostly from case reports, to guide clinicians in managing clozapine alongside anti-tuberculosis therapy (ATT).Literature reviewWe present 5 case reports of patients with schizophrenia or schizoaffective disorder who continued clozapine while receiving ATT. In most of the case reports (n = 3), the ATT regimen included both rifampicin, a CYP450 inducer, and isoniazid, a CYP450 inhibitor. We also review pharmacokinetic properties of rifampicin and the potential impact of rifamycin-based regimens on clozapine metabolism and levels.Case presentationWe present the case of a 35-year-old prescribed clozapine for 4 years prior to being diagnosed with pulmonary tuberculosis. The patient continued clozapine and was closely followed in both the inpatient and outpatient settings while completing a 6-month course of rifampicin, isoniazid, pyrazinamide, and ethambutol. During ATT, the patient had clozapine and norclozapine levels measured at least once monthly and maintained stability in their psychiatric symptoms through adjustment of clozapine and adjunctive antipsychotic dosages.ConclusionOur case supports previous reports that ATT can influence clozapine levels. Clozapine dose adjustments will likely be required to maintain clinical stability and prevent adverse effects, but the management appears to be patient-specific. We recommend closely monitoring patients’ clinical status and clozapine levels during and after ATT to optimize outcomes.